2020
DOI: 10.1371/journal.pntd.0008114
|View full text |Cite
|
Sign up to set email alerts
|

Cystic echinococcosis in the Eastern Mediterranean region: Neglected and prevailing!

Abstract: Cystic echinococcosis (CE) is distributed worldwide, extending from China to the Middle East and from Mediterranean countries to the sub-Saharan Africa and South America. According to WHO, one million people around the world are suffering from CE with an estimated burden of 183,573 DALYs. The annual monetary burden of the disease due to treatment costs and CE-related livestock losses has been estimated at US$ 3 billion. CE is endemic in all countries within the WHO Eastern Mediterranean Regional Office (EMRO).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…In accordance with its distribution, several previous studies revealed the endemicity of the disease in Egypt and neighboring countries of the Mediterranean basin and Middle East ( 19 – 30 ). The prevalence rates varied greatly among intermediate hosts of various species because of the influence of a variety of environmental factors and hygienic conditions ( 25 ), which is potentiated by the presence of infected stray dogs that are mostly used for guarding purposes or by the ease access of these dogs to slaughter houses ( 25 , 29 ).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In accordance with its distribution, several previous studies revealed the endemicity of the disease in Egypt and neighboring countries of the Mediterranean basin and Middle East ( 19 – 30 ). The prevalence rates varied greatly among intermediate hosts of various species because of the influence of a variety of environmental factors and hygienic conditions ( 25 ), which is potentiated by the presence of infected stray dogs that are mostly used for guarding purposes or by the ease access of these dogs to slaughter houses ( 25 , 29 ).…”
Section: Introductionsupporting
confidence: 61%
“…The discrepancy in the occurrence of CE in camels and cattle in the present study vs. those reported in several previous studies may be attributed to several factors, such as hygienic practices during slaughter, sex and age of the slaughtered animals, the method of detection, the geographic location, and various climatic conditions ( 25 , 45 , 73 , 74 ). The unhygienic disposal of condemned carcasses and infected organs, the ease of access stray dogs to slaughter houses, and the unauthorized slaughter are also relevant factors in the transmission of CE ( 29 , 30 , 74 , 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cystic echinococcosis (CE) is ranked second in the list of food-borne parasites worldwide, listed among the most severe parasitic diseases in humans (World Health Organization and Food and Agriculture Organization of the United Nations, 2014) and prioritized by the World Health Organization as one of the 17 neglected tropical diseases (WHO, 2015). It is also known to be the most important parasitic zoonosis in the Mediterranean region (Dakkak, 2010;Ismail et al, 2018;Borhani et al, 2020), with stable endemicity in the Middle East due to the high diversity of intermediate hosts, mainly sheep and goats, followed by camels and cattle (Al Kitani et al, 2015). CE is creating a serious public health problem and is a burden to national economy for most countries in this region (Grosso et al, 2012;Thys et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CE is considered to be endemic in all eastern Mediterranean region, and this region is one the major hotspots of CE. Despite this fact, CE is not among the health topic list of diseases in this region which requires more attention [ 4 ]. In Pakistan as one of these countries, CE is also endemic but their data is still limited [ 5 ].…”
Section: Discussionmentioning
confidence: 99%